Peran VPN dalam Menjaga Privasi Pengguna Jaringan Publik - Fauzan Prasetyo Eka Putra; Yogi Setiawan; Samsul Arifin; Wahyu Hidayatullah (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The use of public networks such as free Wi-Fi is increasingly widespread along with the development of information technology. However, public networks have a high level of vulnerability to security threats such as data interception attacks in the center, and session hijacking. This study aims to examine the role of Virtual Private Network (VPN) in maintaining user privacy when accessing public networks. The method used is a literature study with a descriptive qualitative approach, based on academic literature, research reports, and the latest technical documentation. The results of the study show that VPN is able to encrypt data traffic, hide the user's IP address, and prevent unauthorized access to sensitive information. Analysis of VPN protocols such as WireGuard, OpenVPN, and L2TP/IPSec indicates that performance and level of protection vary, with WireGuard showing the highest efficiency. Although effective, the use of VPN also has limitations such as decreased connection speed and privacy risks if using untrusted services. Therefore, choosing the right VPN service and implementing good security policies are very important in efforts to protect digital privacy. This study confirms that VPN is an important component in the cybersecurity ecosystem, especially in the context of public network access.